Peningkatan Produksi dan Kadar Gula Polong Muda Dua Genotipe Kacang Panjang (Vigna sesquipedalis [L.] Koern.) dengan Pemupukan Kalium - Ardian Ardian (Politeknik Negeri Lampung., 2010)
Quality factors intensively noticed by consumers are bean color, bean maturity, length of bean, bean shape, shape of bean surface, bean crispiness, and sweetness of bean.Since, potassium fertilization could increased the quantity and quality of yield some crops.The objectives of this research were to know the characters of production and young bean sweetness in different potassium environments. The treatments were arranged in factorial arrangement (2x4) with 3 replications. First factors were genotype of long bean which were stripped seed (G1) and black seed (G2). Second factors were KCl dosages which were 0 kg.ha-1(K0), 50 kg.ha-1(K1), 100 kg.ha-1(K2), 150 kg.ha-1(K3) dan 200 kg.ha-1(K4). The genotype of stripped seed had superior quality of production, while yield quantity didn tdifferent between genotype. Fertilization of potassium with dosage 50 kg of KCl /ha had increased the quality of yardlong bean crop production. Keywords: Sugar Content Pod , Peanut Genotypes, Potassium Fertilization